Fanny's First Play - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2004)
"Fanny's First Play" by Bernard Shaw is a play written in 1911. A young woman stages her own theatrical work while keeping her authorship secret, hiring professional actors and inviting prominent critics to judge it. The production features a play within a play: the frame satirizes theatre critics through thinly-veiled caricatures, while the inner drama explores what happens when respectable young people from genteel families find themselves in shocking circumstances that challenge their carefully maintained social facades. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Fanny%27s_First_Play
Release date is 2004-05-01
Produced by Ron Burkey, and David Widger
Keywords: English drama